2016
DOI: 10.4257/oeco.2016.2001.06
|View full text |Cite
|
Sign up to set email alerts
|

Small Mammals (Rodentia and Didelphimorphia) From Serra Do Ouro Branco: Southern Portion of Espinhaço Mountain Range, Minas Gerais, Brazil

Abstract: RESUMOA Serra do Ouro Branco, está localizada na porção sul da Cadeia do Espinhaço, região de transição entre o Cerrado e a Mata Atlântica, no estado de Minas Gerais, Brasil. O objetivo deste estudo foi inventariar os pequenos mamíferos do Parque Estadual da Serra do Ouro Branco (PESOB) e do Monumento Natural Estadual de Itatiaia, unidades de conservação da Serra do Ouro Branco, e comparar com a diversidade encontrada em outras áreas da Cadeia do Espinhaço. A amostragem durou 24 meses (2009)(2010) utilizando p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Bonvicino et al 2002, Geise & Astúa 2009, Pereira & Geise 2009, Paglia et al 2012, Nogueira et al 2015, Patton et al 2015. A similar pattern represented by species shared with Atlantic Forest, Caatinga and Cerrado was observed in other studies carried on the Espinhaço Range (see Pereira & Geise 2007, 2009, Câmara & Oliveira 2012, Braga et al 2016 which is a contact zone between the Cerrado and Atlantic Forest to the south and a transition zone between the Cerrado, Atlantic Forest and Caatinga in the northern (Giulietti et al 1997).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Bonvicino et al 2002, Geise & Astúa 2009, Pereira & Geise 2009, Paglia et al 2012, Nogueira et al 2015, Patton et al 2015. A similar pattern represented by species shared with Atlantic Forest, Caatinga and Cerrado was observed in other studies carried on the Espinhaço Range (see Pereira & Geise 2007, 2009, Câmara & Oliveira 2012, Braga et al 2016 which is a contact zone between the Cerrado and Atlantic Forest to the south and a transition zone between the Cerrado, Atlantic Forest and Caatinga in the northern (Giulietti et al 1997).…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, Câmara & Oliveira (2012) reported one of the largest species richness in the Central Espinhaço (n = 24), both studies using only wire traps. Indeed, the species composition of PERP was grouped with other areas at the Central Espinhaço (Leal et al 2008, Câmara & Oliveira 2012, showing greater similarity in species composition in relation to the Serra de Ouro Branco (Braga et al 2016), localized at the Southern Espinhaço. Despite the greater similarity in species composition between the three areas located in the Central Espinhaço, they present heterogeneous vegetation formations, composed of different physiognomies from Cerrado such as rock grassland, Cerrado stricto sensu, woodland savanna, and riparian forests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in recent years of new small mammal's records in campos rupestres areas at the Espinhaço Mountain Range is noteworthy, and has provided important data on its distribution, taxonomy and ecology (see Pereira & Geise, 2009;Pardiñas et al, 2014;Loss et al, 2015;Braga et al, 2016). Nevertheless, the current level of knowledge on the composition and distribution of Phyllotini rodents in habiting rock outcrops in campos rupestres across this wide re-.49 gion is still scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the conservation of the local biodiversity depends on combined efforts between local communities and environmental agencies (Brasil 2000). Studies conducted in these CUs revealed high richness of amphibians (São Pedro & Feio 2011), lizards , and small mammals (Braga et al 2016). The fauna of small mammals includes rare species not found in other studied areas of the Espinhaço Mountain Range (Braga et al 2016).…”
Section: Introductionmentioning
confidence: 89%